Implementasi Load Balancing dengan Metode Policy Based Route dan Efek Failover untuk Optimalisasi Jaringan Internet - Lalitya Nindita Sahenda; Prayugo Ardi Wibowo (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2024)
The rapidly developing internet has a positive impact on various sectors globally, including the impact on the world of education. In the field of formal education, the internet is not only used as an active learning media, but also as a media for conducting online-based exams, for example in conducting semester exams. SMK PPN 1 Tegalampel as a formal educational institution also uses the internet to support learning and teaching activities. Therefore, the internet is a very essential need in this school. Internet network management is very necessary in efforts to provide internet quality. One way to manage internet networks is to implement load balancing. Load balancing is applied to divide the network load between two different ISPs so that it is not overloaded. The load balancing method applied at SMK PPN 1 Tegalampel is policy Based Route (PBR). PBR divides the network load according to the policy or rules set by the network technician. Apart from loading balancing, office failover is also implemented in the school internet network. So if an ISP connection is lost, it will automatically be diverted to the backup line. With this failover effect, it guarantees that an internet connection will always be available even if the ISP is disconnected.